Data Acquisition Recent Advances and Applications in Biomedical Engineering - Płaczek, Bartłomiej (Biomedical Engineering, 2021)
Recent advances in sensor design, embedded systems, and communication networks allow us to collect valuable biomedical data effectively. The new biomedical data acquisition systems make significant contributions to life quality as well as support healthcare and diagnostic procedures. This book presents several innovative applications of data acquisition technology for monitoring patient activity, assisted living, diagnosing osteoarthritis, recognizing disorders of the cardiovascular system, and designing prostheses for amputees.